Co-designing an Indicator of Habitat Connectivity for England - Mancini, Francesca; Hodgson, Jenny A.; Isaac, Nick J. B. (Frontiers in Ecology and Evolution, 2022)
Landscapes have been drastically transformed by human activities, generally resulting in the loss of semi-natural habitat. In the UK, wildlife habitat mainly consists of small patches of semi-natural habitat that are poorly connected to each other. In May 2019 the UK Government published an outcome indicator framework for measuring progress against the goals and outcomes of the 25 Year Environment Plan (YEP) for England. The indicator of the Quantity, Quality and Connectivity of Habitats (D1) is one of seven indicators within the Wildlife theme and it follows the principle of making areas of semi-natural habitat “more, bigger, better and joined up”. In this study, we describe the process of co-designing the connectivity metric for indicator D1. In consultation with experts and stakeholders we selected three candidate landscape connectivity metrics to produce the indicator. The first metric comes from a suite of rules of thumb for practitioners and it is the proportion of habitat patches in the landscape that have a nearest neighbour ≤ 1Km away. The second metric is a habitat fragmentation index from the Natural England National Biodiversity Climate Change Vulnerability Assessment Tool (NBCCVAT). The third and final metric is from the software Condatis and it represents the ability of a species to move through a landscape. We tested each metric on a set of simulated landscapes representing different levels of habitat addition strategies and different spatial configurations. We asked if the metrics are able to detect changes in the connectivity of each of these landscapes after habitat addition. Two of the three metrics (NBVVCAT and Condatis) performed well and were sensitive to change. They both increased as the total extent of habitat increased and each showed particular sensitivity to one spatial arrangement over the other. Given these results, one or both of these metrics could be used to produce the indicator. We discuss the implications of using one or both of the metrics and highlight the fundamental choices that need to be made to produce the indicator.